KUALITAS LAPORAN KEUANGAN PEMERINTAH KOTA PALEMBANG: DARI ASPEK SISTEM PENGENDALIAN INTERNAL - Fildzah Rahmah Satirah; Rita Martini; Nurhasanah Nurhasanah; Kartini binti Che Ibrahim; Kartika Rachman Sari; Farida Husin (EKSISTANSI, 2022)
The internal control system is one of the variables that can help to improve the quality of government financial statement data (SPI). The purpose of this study is to see how the internal control mechanism at Palembang City's Regional Secretariat affects the quality of financial reports. The responses to the distributed questionnaires are collected, and data processing begins. Staff from the Palembang City Regional Secretariat's twelve sectors were polled. Sixty people responded to the survey, and sixty of them provided feedback. Linear regression was used as an analytical tool. The study's findings show that internal control has a favorable and significant impact on financial statement information quality